2014
DOI: 10.1177/0148607114549254
|View full text |Cite
|
Sign up to set email alerts
|

What Are Adults With Inflammatory Bowel Disease (IBD) Eating? A Closer Look at the Dietary Habits of a Population‐Based Canadian IBD Cohort

Abstract: Food avoidance is common among those with IBD but may be due more to personal preferences, while sugar-laden beverages may be displacing other foods higher in nutrients. The overall diet of patients with IBD differed from that of the non-IBD Canadian population, but deficiencies were observed in both groups. Considering malnutrition among persons living with IBD, nutrition education by trained dietitians as part of the IBD team is imperative to address food avoidance and overall balance nutrition as part of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
79
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 25 publications
10
79
2
3
Order By: Relevance
“…Often leafy or non-leafy vegetables, fruits, dairy, alcohol, red meat or fast food were avoided [12,33]. This is in accordance with our data, since 35% of our patients with IBD stated to have reduced the consumption of fast food compared to only 7% in the healthy control group.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Often leafy or non-leafy vegetables, fruits, dairy, alcohol, red meat or fast food were avoided [12,33]. This is in accordance with our data, since 35% of our patients with IBD stated to have reduced the consumption of fast food compared to only 7% in the healthy control group.…”
Section: Discussionsupporting
confidence: 90%
“…Many patients with IBD suppose that the diet influences the course of their disease or even cause a relapse [11,33]. Therefore, patients often start dietary changes and avoid "trigger foods" which might worsen their symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a high intake of meat correlates with UC incidence and relapse (26). Furthermore, studies have demonstrated that a high intake of linoleic acid, a polyunsaturated omega-6 fatty acid present in meat, increases IBD risk (26,27). Previous meta-analyses have also revealed that consumption of processed meat increases cancer risk (7,9,10).…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian study reported that IBD patients avoid alcohol, popcorn, legumes, nuts, seeds, deep-fried food, and processed meat [16]. Patients with active IBD also consumed significantly more portions of sports drinks and sweetened beverages compared with those with inactive disease [16].…”
mentioning
confidence: 99%